(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Percutaneous coronary intervention (PCI) has comorbid conditions that significantly impact clinical outcomes in such patients. The correlation between comorbidities and mortality is critical in understanding how best to manage patients and enhance the chances of survival among high-risk cardiac patients. Objective: To establish the effects of comorbid states on in-hospital and short-term mortality in patients receiving PCI at the Armed Forces Institute of Cardiology (AFIC/NIHD), Rawalpindi, Pakistan. Methods: This study was conducted as a cross-sectional study at Armed Forces Institute of Cardiology (AFIC/NIHD), Rawalpindi, Pakistan between the period of February, 2025 to June, 2025 and involved 420 patients who underwent PCI. Data on demographic, comorbidity, and mortality outcomes was obtained using hospital records. The chi-square tests and logistic regression were used to conduct the statistical analyses with the assistance of SPSS 28.0 to identify the independent predictors of mortality. Results: The in-hospital mortality was 6.9%, and the 30-day postoperative mortality was 8.3%. The most effective predictors of mortality were chronic kidney disease (CKD) and heart failure (OR: 2.83 and 2.41, respectively; p<0.01). Patients who had three or greater comorbidities had a rate of 14.5% mortality as opposed to 3.2% in patients without comorbidities (p<0.001). Diabetes mellitus was also weakly, though significantly, related to mortality (p=0.041). Conclusion: Comorbidities, especially CKD, heart failure, and diabetes mellitus, are important causes of death among patients who experience PCI. The risk increases depending on the number of underlying diseases, which is why it is necessary to thoroughly evaluate the patient before the procedure and have multidisciplinary control. Risk stratification tools and preventive strategies can be integrated to achieve better outcomes with high-risk cardiac patients in Pakistan.